The Effect of Phototherapy on Serum Calcium and Magnesium Level in Newborns Gestational Age 36 Weeks and Above - Ishfaq, Hadia; Kafi, Nisreen (Pakistan Armed Forces Medical Journal, 2022)
Objective: To investigate the phototherapy effect on serum calcium and magnesium levels of children with gestational age 36 weeks or above. Study Design: Cross-sectional analytical study. Place and Duration of Study: Department of Pediatric, King Fahad Armed Forces Hospital, Jeddah from Jan to Sep 2019. Methodology: Total of 200 participants were recruited into the study after obtaining informed consent. Patients’ characteristics were obtained from medical record file. Their mothers were interviewed. Before phototherapy, laboratory investigations were done. Phototherapy was performed with conventional method 410-417mm wave length was maintained and patients was kept at distance of 20cm. After phototherapy completion, laboratory investigations were repeated and difference was noted. Results: Out of 200 patients, 54% were males and 46% were females. Average age of patients was 1.85 ± 0.96 days with range 0-5 days. Decrease in calcium and magnesium levels was observed in 64 (32%) and 49 (24.5%) patients respectively following phototherapy completion. There was statistically significant mean difference in calcium and magnesium levels after phototherapy and bilirubin was also significantly decreased. Conclusion: Decrease was observed in calcium and magnesium levels following phototherapy. Phototherapy may lead to decrease levels of calcium and magnesium, hence frequent assay warranted. Further investigations should be conducted in our region enrolling only neonates to confirm phototherapy induced hypocalcaemia and hypomagnesaemia.